2021
DOI: 10.1093/ecco-jcc/jjab073.040
|View full text |Cite
|
Sign up to set email alerts
|

DOP01 Efficacy and safety of the IL-6 trans-signalling inhibitor olamkicept: a phase 2 randomized, placebo-controlled trial in moderately to severely active Ulcerative Colitis

Abstract: Background Total inhibition of IL-6 or its receptor represents a potent anti-inflammatory therapy with considerable side effects. Selective targeting IL-6 trans-signalling may have safety advantages that differentiates it from current pan-IL-6 inhibitors. We evaluated the efficacy and safety of olamkicept, a soluble gp130-Fc fusion protein that binds to the IL-6 and soluble IL-6 receptor complex, as induction therapy for active ulcerative colitis (UC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…After 12 weeks with injections every second week, clinical remission was seen in 0% (placebo), 6.7% (olamkicept 300 mg/injection) and 20.7% (olamkicept 600 mg/injection) of the patients. At the same time, mucosal healing occurred in 3.4% (placebo), 10% (olamkicept 300 mg/injection) and 34.5% (olamkicept 600 mg/injection) of the patients 115 . Based on the positive results of these phase II clinical trials, phase III clinical trials are being planned for the near future.…”
Section: Preclinical and Clinical Development Of Olamkiceptmentioning
confidence: 90%
“…After 12 weeks with injections every second week, clinical remission was seen in 0% (placebo), 6.7% (olamkicept 300 mg/injection) and 20.7% (olamkicept 600 mg/injection) of the patients. At the same time, mucosal healing occurred in 3.4% (placebo), 10% (olamkicept 300 mg/injection) and 34.5% (olamkicept 600 mg/injection) of the patients 115 . Based on the positive results of these phase II clinical trials, phase III clinical trials are being planned for the near future.…”
Section: Preclinical and Clinical Development Of Olamkiceptmentioning
confidence: 90%
“…Interestingly, we have found that QT prolongation due to overactivated IL-6 trans-signaling can be prevented with olamkicept, highlighting an emerging and important anti-arrhythmic role for olamkicept in obesity arrhythmias. Notably, olamkicept has shown encouraging results in phase II clinical studies for inflammatory bowel disease [7,[88][89][90][91], and thus further provides the rationale to refine olamkicept for the development of the next generation of proinflammatory cytokine inhibitors as an antiarrhythmic in the setting of obesity.…”
Section: Discussionmentioning
confidence: 99%